Monitoring of Drinking Water Quality of Nagpur City, Maharashtra, India During August to October 2001 - Shelke, M.E.; Tayade, D.T.; Shelke, R.E. (Asian Journal of Chemistry, 2010)
Nagpur city is an important city in India. The largest industrial estate in Asia of approx. 6,000 hectares is being developed at Butibori, close to Nagpur. So different kinds of pollution, viz., water pollution, air pollution, soil pollution have been created due to lack of knowledge, negligence and illiteracy. It is observed that the study of water quality is of enormous educational value for the quality of water. Hence it was thought interesting to study the physico-chemical parameters of water. The suitability of water for drinking and other domestic purposes is studied by collecting samples from wells situated in various zones of Nagpur city (Maharashtra). The parameters were analysed and compared with standard values prescribed by American Public Health Association (APRA) and World Health Organisation (WHO).